2016
DOI: 10.1637/11294-100615-reg
|View full text |Cite
|
Sign up to set email alerts
|

Variability Assessment of California Infectious Bronchitis Virus Variants

Abstract: On the basis of the data from the California Animal Health and Food Safety Laboratory System, 1444 infectious bronchitis (IB) cases were diagnosed between 1997 and 2012. Epidemiologic analyses demonstrated two major IB virus (IBV) outbreak peaks, affecting mainly 35-to-49-day-old broiler chickens. California variant 1737 (CA1737) and California variant 1999 (Cal 99) IBV types were the most prevalent genotypes during the analyzed period. To further understand the increased prevalence of these genotypes, we asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…At the genomic level, these differences can be greater or equal to 5% in the hypervariable region of the S1 gene. These variant strains are usually restricted to geographic regions and most of the time are transient (Gallardo et al 2016), reason why diagnostics and epidemiological surveillance are crucial to determine their existence and persistence. This strategy helps planning preventative measures in the field.…”
Section: Infectious Bronchitis Virusmentioning
confidence: 99%
See 4 more Smart Citations
“…At the genomic level, these differences can be greater or equal to 5% in the hypervariable region of the S1 gene. These variant strains are usually restricted to geographic regions and most of the time are transient (Gallardo et al 2016), reason why diagnostics and epidemiological surveillance are crucial to determine their existence and persistence. This strategy helps planning preventative measures in the field.…”
Section: Infectious Bronchitis Virusmentioning
confidence: 99%
“…ArkDPI vaccines showing higher heterogeneity have been associated with respiratory signs and tracheal damage (Ndegwa et al 2012). Studies in variant IBV variability have shown different levels of heterogeneity in different IBV genotypes (Gallardo et al 2016). It is important to understand the heterogeneity of variant IBV strains before selecting them as vaccine candidates.…”
Section: Vaccines and Their Usementioning
confidence: 99%
See 3 more Smart Citations